Implementation and Evaluation of Public Policies for promoting physical activity in older adults: A scoping review protocol (Research, Society and Development, 2025)
Objective: To synthesize the knowledge on the implementation and evaluation of public policies aimed at promoting physical activity among older adults in community settings. Method: A scoping review protocol developed using the five-stage methodology by Arksey and O'Malley. A systematic search will be conducted across eight databases (PubMed, MEDLINE, CINAHL, Embase, Web of Science, Scopus, Biblioteca Virtual de Salud, LILACS, La Referencia) using MeSH terms and natural language related to the research question. Articles published in English, Portuguese, or Spanish that meet the selection criteria will be included. No restrictions will be applied regarding publication date or geographic location. Results: The results will be presented descriptively through data extraction from each document included. A synthesis of the findings will be conducted using both quantitative and qualitative analysis. Conclusion: This protocol will serve as a guide for developing a scoping review that enables a critical synthesis of the literature on the implementation and evaluation of public policies aimed at promoting physical activity among older adults.